(untitled) (International Journal of Engineering and Computer Science, 2018)
cloud computing is an emerging technology and serves as next generation platform, which allows the user to pay as they use. It permits access to remote and geographically distributed resources with the help of an important feature in cloud computing called virtualization. Cloud consists of number of virtual machines. In cloud there is need of number of virtual machines (VM) based on the requirement of user and cloud service providers. Scheduling is necessary to manage large number of VM requests. Scheduling is key technology in cloud computing, scheduling of tasks and resource allocation is challenging task in cloud. So we require scheduling algorithm. Primary consideration of scheduling algorithm is to provide proficiency to task and resource scheduling. Main objective of the paper is to give comparative analysis of existing scheduling algorithm in cloud platform where resources have varying cost and computational efficiency. In this paper we have surveyed on different types of scheduling algorithm and tabulated their various parameters, scheduling factors and so on.